Accumulation mechanism and model of coal measure derived oil and gas in the deep reservoir of Huanghua Depression, Bohai Bay Basin, China - Runze Yang; Haitao Liu; Hongjun Li; Changyi Zhao; Chuanming Li (Journal of Natural Gas Geoscience, 2022)
Hydrocarbon accumulation in coal measure strata is consist of several types which includes intra-source accumulation and adjusted accumulation, particularly in basins that had experienced multi-stage tectonic activities. The mechanism governing this accumulation is extremely complex. Using the Paleozoic petroleum system in the Huanghua Depression as an example, the mechanism of hydrocarbon accumulation in deep reservoirs can be revealed by means of core observation, geochemistry testing of coal measure source rock, thin section observation, fluid inclusions testing, and profile analysis of typical reservoirs, combined with the burial and thermal history of strata. Based on the regional tectonic, the mechanism of hydrocarbon accumulation in coal measures is defined and the accumulation model was established. The results show that the Paleozoic petroleum system in the Huanghua Depression has three different types of source-reservoir-cap assemblages: under-source, intra-source, and above-source assemblage. Regional tectonic evolution controlled the hydrocarbon generation process of source rocks, showing the hydrocarbon generation characteristics of “oil in the early stage and gas in the late stage.” The Middle Cretaceous is the first of two periods of hydrocarbon accumulation, during which stage occurred in low-maturity oil and a small amount of natural gas were mainly stored in intergranular pores and dissolution pores. The tectonic uplift in the Late Cretaceous caused the destruction of the ancient reservoir. The second accumulation stage occurred in the Middle Paleogene to the present. A large amount of natural gas and high maturity oil were mostly stored in dissolution pores and structural fractures. The hydrocarbon accumulation in Huanghua Depression was simultaneously regulated by reservoir reformation, tectonic activities, and source rock maturation. Based on the foregoing understanding, the hydrocarbon accumulation model of “oil and gas transfer station” in coal measures is put forward, that is, oil and gas are first accumulated in intra-source or near-source reservoirs, and are then adjusted from this “oil and gas transfer station” to other areas as a result of tectonic activity.